Biological activity of dendrimer–methylglyoxal complexes for improved therapeutic efficacy against malignant cells. Issue 8 (18th January 2016) - Ghosh, Srabanti; Chakraborty, Prabal; Chakrabarti, Adrita; Ghosh, Manosij; Mandal, Amit; Saha, Partha; Mukherjee, Anita; Acharya, Somobrata; Ray, Manju
Abstract : A facile strategy to synthesize polymer based conjugation of methylglyoxal which demonstrated inhibition against malignant cells with desired selectivity can revolutionize the cancer treatment via minimizing the human health risks. Abstract : The clinical application of methylglyoxal (MG, a normal human metabolite) for cancer therapy is limited by its facile enzymatic degradation. The present investigation was aimed at exploring the potential anticancer therapy of methylglyoxal loaded polyamidoamine (PAMAM) dendrimers with different terminal groups (PAMAM/MG). Uniform PAMAM-NH2 /MG with an average particle size of 55 ± 5 nm and high encapsulation efficiencies (EE) of 82 ± 2% have been characterized by transmission electron microscopy (TEM) and spectroscopic techniques. Compared to the free MG, a slow release of MG from the dendrimer complex was ∼85 ± 2% after 24 hours, suggesting the potential of the dendrimers as a sustained drug delivery system. PAMAM-NH2 /MG possesses biocompatibility with no hemolytic activity and is highly effective in growth inhibition of mice carcinoma and sarcoma cells. PAMAM-NH2 /MG selectively reduced cell viability of Hela cells with an IC50 value of 0.4 ± 0.15 μg mL −1 while more than 90% of normal fibroblast cells have been found to be viable at a similar dose. Interestingly, even a lower dose of MG (∼250 times) in PAMAM-NH2 /MG can effectively target Hela cells in comparison to free MG. TEM images demonstrated the ultra structural changes of Hela cells after being treated with PAMAM-NH2 /MG and also confirmed cellular uptake. DNA damage as measured by comet assay was found to be dose dependent for mice carcinoma and sarcoma cells but no such genotoxic response was observed in human lymphocytes, after treatment with PAMAM-NH2 /MG. Thus, dendrimer encapsulated MG might be an effective strategy to target the cancer cells and further improvements of the surface functionality of dendrimers can be used as a valuable tool for the development of novel therapeutics in nano-oncology.